2014
DOI: 10.3109/01658107.2014.957780
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Motor Outcomes of Strabismus Surgery for Chronic Isolated Adult Sixth Nerve Palsy

Abstract: Abducens nerve palsy is the most common acquired ocular motor nerve palsy in adults. Chronic cases of abducens palsy often require surgical intervention to relieve disabling diplopia. The goal of this study was to identify factors associated with surgical outcomes in isolated abducens palsy. Medical records of all adult patients from 1988 to 2012 with abducens palsies who underwent strabismus procedures were retrospectively reviewed. Motor alignment, extraocular motility, and sensory outcomes were recorded. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
1
8
0
3
Order By: Relevance
“…Nevertheless, the average number of operations (1.3) is not considered to be a high risk for reoperation, compared with other forms of incomitant strabismus. 9,10 The success rate for Peragallo et al 19 was 58% by surgery alone, but they did not use prism therapy. In an earlier report 20 on abducens palsy, the surgical success rate was 52%, but when that same study allowed the use of prisms or small face turns to correct diplopia, the success rate reached 75%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the average number of operations (1.3) is not considered to be a high risk for reoperation, compared with other forms of incomitant strabismus. 9,10 The success rate for Peragallo et al 19 was 58% by surgery alone, but they did not use prism therapy. In an earlier report 20 on abducens palsy, the surgical success rate was 52%, but when that same study allowed the use of prisms or small face turns to correct diplopia, the success rate reached 75%.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports, 12 , 18 abducens palsy was the most frequent cause of acquired paralytic strabismus among adults, and abducens palsy was also the most frequent strabismus after severe brain disease in our study, reaching 53% in the BT group. A study of 81 cases by Peragallo et al 19 demonstrated that patients with traumatic or neoplastic causes had a higher rate of complete abducens palsy, in comparison to other etiologies (58% versus 24%, respectively), and required more surgical procedures to achieve a successful outcome (48%). In this study, complete abducens palsy accounted for 53% of patients with abducens palsy who underwent muscle transposition, and, furthermore, severe vertical deviation was found in 33% and cyclotorsion was found in 36%, suggesting that strabismus after severe brain disease might be refractory.…”
Section: Discussionmentioning
confidence: 99%
“…In der Verlaufskontrolle verringerte sich der Tieferstand bei 6 der 7 Patienten auf < 5,0°. Peragallo et al fanden im Verlauf keine Vertikaltropien bei 9 Patienten nach modifizierter Hummelsheim-Operation (5 davon mit M.-rectus-internus-Rücklagerung) [14]. Wird eine posteriore Fixationsnaht benutzt, so steigt das Risiko für postoperative VDs deutlich an [22].…”
Section: Diskussionunclassified
“…Die Pareseursache der 3 Patienten, die wegen einer Unterkorrektur im Verlauf Revisionen erhielten, war in 2 Fällen eine Tumorerkrankung, in 1 Fall ein Schädel-Hirn-Trauma. Auch Peragallo et al berichten über ein erhöhtes Risiko für Reoperationen bei zugrunde liegender neoplastischer oder traumatischer Erkrankung [14].…”
Section: Diskussionunclassified
See 1 more Smart Citation